Effect of standardized post-coercion review on subjective coercion: Results of a randomized-controlled trial. Issue 1 (7th December 2021) - Wullschleger, A.; Vandamme, A.; Mielau, J.; Stoll, L.; Heinz, A.; Bermpohl, F.; Bechdolf, A.; Stelzig, M.; Hardt, O.; Hauth, I.; Holthoff-Detto, V.; Mahler, L.; et al.
Abstract: Background: Post-coercion review has been increasingly regarded as a useful intervention in psychiatric inpatient setting. However, little is known about its effect on perceived coercion. Methods: A multicenter, two-armed, randomized controlled trial was conducted, aiming at analyzing the effect of post-coercion review on perceived coercion. People with severe mental disorders, who experienced at least one coercive measure during inpatient treatment, were randomized using Zelen's design to an intervention group receiving standardized post-coercion review, or a control group treated as usual. The MacArthur admission experience scale (AES) and the coercion ladder (CL) were used to assess perceived coercion during inpatient treatment. The coercion experience scale (CES) measured experienced coercion during the coercive intervention. Analyses of covariance were performed to determine group differences. Results: Of 422 randomized participants, n = 109 consented to participate in the trial. A restricted intention-to-treat analysis of all individuals who consented revealed no significant effect of the intervention on perceived coercion. A significant interaction effect between the factors gender and intervention on the AES scores was found. Sensitivity analysis revealed significant effects of the intervention on both AES and CL scores and an interaction effect between intervention and gender, indicating a higher efficacy in women. No effect of the intervention on CES scores was found. Conclusions: Standardized post-coercion review sessions did not alleviate the subjective perception of coercion in the total sample. However, post hoc analysis revealed a significant effect of the intervention in women. Results indicate the need to further address gender-specific issues related to coercion.